Forced convection nanofluids through corrugated backward facing step channels using numerical analysis - Mohammed, Kafel Abdulazeez (2017)
Due to the importance of heat exchangers in various engineering applications, it is crucial to develop compact, lightweight heat exchangers with high thermal efficiency and low manufacturing cost. Much effort has been made to significantly enhance heat transfer and this can be achieved by designing corrugated walls for the heat exchanger channels. For this purpose, corrugated backward facing step wall is one of the many suitable techniques to enhance the heat transfer in heat exchangers. When fluid flows in a corrugated facing wall, the flow becomes disturbed due to growing re-circulation regions near the corrugated wall, which enhances the mixing of fluid as well as heat transfer. In this research, numerical modelling is carried out using ANSYS/FLUENT 15.0 software. The continuity, momentum and energy equations are discretized and solved using the finite volume method. The SIMPLE algorithm scheme is applied to link the pressure and velocity fields inside the domain. In the current work, the flow and heat transfer of nanofluids in corrugated facing channels are examined numerically. Five different types of nanofluids such as Al2O3, CuO, SiO2, ZnO and Hamzel® silica aerogel-water with nanoparticle diameters in the range of 25 to 80 nm and the range of nanoparticle volume fraction from 0 to 4% are examined. The effects of geometrical parameters such as the amplitude height and wavelength of corrugated facing step channels in addition to the effect of Reynolds number on the flow and thermal fields are presented and analyzed. Comparisons of the numerical results with those available in the literature have been presented and a good agreement between the results is observed. The Reynolds number is varied between 100–1,500 and 5,000– 20,000 for laminar and turbulent flows, respectively.In general, the average Nusselt number and pressure drop increase with an increase in the amplitude height and nanoparticle concentration. However, there is a decrease in these parameters with an increase in the wavelength and nanoparticle diameter. The silicon dioxide-water nanofluid provides the best thermal hydraulic performance. The trapezoidal corrugated facing step channel provides the best thermal-hydraulic performance at an amplitude height of 4 mm, followed by the triangular corrugated facing step channel. The simulation results conform well with those in the literature. Simulations are also conducted to examine the effect of nanoparticle concentration (0, 1, and 4%) and channel shape on the average Nusselt number and pressure drop for Hamzel® silica aerogel-water nanofluid in the laminar flow region. This novel nanofluid is a promising working fluid for heat exchangers due to its significant heat transfer enhancement when coupled with the trapezoidal corrugated facing step channel. This is indeed expected because of the high thermal conductivity and low density of this nanofluid. The Nusselt number enhancement ratio reached to 80% and 85% when using Hamzel® silica aerogel-water in the trapezoidal-corrugate at Nanoparticle concentrations of 1% and 4% respectively. The trapezoidal-corrugate provides the highest thermal-hydraulic performance at amplitude height of 4mm and 2cm wavelength flowed by a triangle having the same property.